2006
DOI: 10.1186/ar2036
|View full text |Cite
|
Sign up to set email alerts
|

Presence of antibodies against cyclic citrullinated peptides in patients with 'rhupus': a cross-sectional study

Abstract: Abstract'Rhupus' is a rare condition sharing features of rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). If rhupus is a distinctive entity, an overlap between RA and SLE or a subset of SLE is currently debated. This study was performed to explore the prevalence of antibodies against cyclic citrullinated peptides (anti-CCP antibodies) in rhupus. Patients meeting American College of Rheumatology criteria for RA, SLE, or both were included. Clinical and radiographic features were recorded and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…The term “Rhupus syndrome” is used to describe the coexistence of SLE and RA, wherein patients have symmetrical erosive arthritis and characteristic manifestations of SLE. 7 The definition of Rhupus syndrome remains controversial, as the immunopathological process of SLE is considered to be the exact opposite of RA. Abnormal activation of T helper type 2 cell (Th2) cytokines plays a central role in SLE while T helper type 1 cells (Th1) participate in RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term “Rhupus syndrome” is used to describe the coexistence of SLE and RA, wherein patients have symmetrical erosive arthritis and characteristic manifestations of SLE. 7 The definition of Rhupus syndrome remains controversial, as the immunopathological process of SLE is considered to be the exact opposite of RA. Abnormal activation of T helper type 2 cell (Th2) cytokines plays a central role in SLE while T helper type 1 cells (Th1) participate in RA.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Some rheumatologists have classified Rhupus syndrome as a subset of SLE with severe arthritis. 7 , 12 SLE shows three types of articular involvement: intermittent nonerosive polyarthritis usually found in the hands, wrists, and knees; nonerosive deforming arthritis referred to as Jaccoud’s joint; and arthritis with joint deformities and specific erosion, that is, Rhupus syndrome. 13 Most patients with SLE have transient, migratory, and reversible arthritis without erosion.…”
Section: Discussionmentioning
confidence: 99%
“…There are three viewpoints on RHUPUS. Some authors such as Fernandez believe that RHUPUS arthropathy is a serious articular involvement of lupus and it is different from a superposition or overlap of RA and SLE [16, 17], while other authors believe that RHUPUS syndrome is combination of SLE and chronic erosive polyarthritis [5, 9, 15], and the last group believes that RHUPUS is overlap of RA or JIA and SLE (regardless to poly or oligoarthritis and erosive or nonerosive) [4, 18]. We agree with last group about RHUPUS syndrome in children.…”
Section: Discussionmentioning
confidence: 99%
“…In our case report, one case had erosive arthritis before completing JSLE, and in our litrature review, just 45% cases had joint erosion (Table 1). Recently, Amezcua-Guerra studied the prevalence of antibodies against anti-CCP antibodies in RHUPUS [18], and they concluded that RHUPUS is an overlap between RA and SLE. …”
Section: Discussionmentioning
confidence: 99%
“…For example, in systemic lupus, ACPA positivity is associated with “rhupus” in which the signs and symptoms of RA prevail. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%